Association between left atrial remodeling and early renal impairment in asymptomatic patients with type 2 diabetes - Mingxia Gong; Min Xu; Suoya Pan; Xiaohong Jiang (BMC Cardiovascular Disorders)
Abstract Background and aims To quantitatively assess the alterations in left atrial morphology and function in patients with asymptomatic type 2 diabetes mellitus (T2DM) via 4D-Auto Left Atrial Quantification analysis (4D Auto LAQ), investigate their correlation with diabetic nephropathy (DN), and evaluate the predictive value for major adverse cardiovascular event (MACE). Methods A cohort of 449 asymptomatic T2DM patients was categorized into four groups: those without DN(G0) and those with DN, which was further subdivided into stages G1, G2, and G3. Through 4D-Auto LAQ analysis, we quantified the left atrial (LA) volume as well as the longitudinal and circumferential strains during the reservoir, conduit, and contraction phases. Additionally, we investigated the association between LA volume, strain parameters, and glomerular filtration rate (GFR). Among the participants, 190 patients in the DN group were followed up. The primary endpoint for follow-up was defined as the first occurrence of non-fatal acute myocardial infarction, stroke, congestive heart failure, or cardiac death. Results (1) Analysis of variance indicated no statistically significant differences in echocardiographic data for left ventricular size or function across groups. (2) Correlation analysis after multivariable adjustment revealed that the LA minimal volume index (LAVImin) increased with the progression of DN, while the absolute value of the LA strain index(reservoir and conduit period) decreased as renal damage worsened, exhibiting a highly significant correlation with the GFR (P < 0.01). (3) Univariate and multivariate Cox regression analyses revealed that: LAVmin, LASr, GFR, and HbA1c were associated with MACEs in patients with DN. Incorporating LAVmin and LASr into the basic model significantly enhanced the predictive value for MACEs in DN patients (with an area under the curve (AUC) of 0.818, sensitivity of 78.6%, specificity of 85.4%). Conclusion The increase in LA volume and weakened reservoir and conduit function in T2DM patients dynamically reflect the severity of renal damage. LAVImin and LASr are associated with the occurrence of MACEs in asymptomatic type 2 diabetes patients with early renal damage. Clinical trial number Not applicable.